P5.15 Preparing for prep: estimating the need for hiv pre-exposure prophylaxis among men who have sex with men using sexual health surveillance data in england. (8th July 2017) - Mitchell, Holly; Desai, Sarika; Mohammed, Hamish; Ong, Koh Jun; Furegato, Martina; Field, Nigel; Gill, O Noel
Abstract : Introduction: To inform public health planning for a large-scale PrEP trial in England, we estimated the need for HIV pre-exposure prophylaxis (PrEP) among men who have sex with men (MSM) attending sexual health clinics. Methods: National STI surveillance data from the genitourinary medicine clinic activity dataset (GUMCADv2) were used to estimate the annual number of HIV-negative MSM who had a HIV test in the past year (which will be a criterion for accessing PrEP in England), for 2010–2015. To estimate the number and proportion of all MSM needing PrEP, we used bacterial STI diagnosis in the past year as a proxy for high-risk behaviour, and estimated HIV incidence (per 100 person-years) in both groups. We used these data to understand the likely geographical distribution of MSM who might need PrEP within the 152 English counties. Results: The number of HIV-negative MSM attending sexual health clinics increased by 68% from 69 392 in 2010 to 1 16 546 in 2015, and the number of HIV-negative MSM with a prior HIV test nearly doubled from 14 643 to 29 023 in the same period. Among HIV-negative MSM with a prior HIV test, the number with a recorded bacterial STI (past year) increased from 4365 (30%) in 2010 to 10, 276 (35%) in 2015 (33% on average). HIV incidence among MSM with a prior HIV test was 1.9 (95% CI 1.6–2.2) per 100py compared to 3.3 (2.7–4.0) per 100py in MSM with a prior HIV test and history of bacterial STI. The number of MSM in need of PrEP (according to bacterial STI history) was 200 men in 4% (6/152) of counties. Conclusion: We estimated that the need for PrEP among MSM in England in 2015 might be around 10 000 individuals with an annual HIV incidence of 3%. Need for PrEP was highly concentrated; in most English counties, the number of MSM with a prior HIV test was small, and only 33% of these men might be clinically assessed as eligible for PrEP. These data illustrate how the population need for PrEP might be estimated in advance of a national trial, and will inform future evaluations at a population level.